(untitled) (Italian Journal of Public Health, 2009)
This article gives an insight to the current health insurance system in the Republic of Macedonia. Special emphasis is given to the specificities and practice of both obligatory and voluntary health insurance, to the scope of the insured persons and their benefits and obligations, the way of calculating and payment of the contributions and the other sources of revenues for health insurance, user participation in health care expenses, payment to the health care providers and some other aspects of realization of health insurance in practice. According to the Health Insurance Law, which was adopted in March 2000, a person can become an insured to the Health Insurance Fund on various modalities. More than 90% of the citizens are eligible to the obligatory health insurance, which provides a broad scope of basic health care benefits. Till end of 2008 payroll contributions were equal to 9.2%, and from January 1st, 2009 are equal to 7.5% of gross earned wages and almost 60% of health sector revenues are derived from them. Within the autonomy and scope of activities of the Health Insurance Fund the structures of the revenues and expenditures are presented. Health financing and reform of the payment to health care providers are of high importance within the ongoing health care reform in Macedonia. It is expected that the newly introduced methods of payments at the primary health care level (capitation) and at the hospital sector (global budgeting, DRGs) will lead to increased equity, efficiency and quality of health care in hospitals and overall system.